Engaging with Citizens to Improve Services - World Bank (New Delhi, 2014)
This study explains why and how the creation of institutionalized citizen engagement will enhance public accountability, performance, and customer responsiveness in the Indian urban water and sanitation sector. It draws on ten practical case studies of citizen engagement in India to derive lessons for civil society groups, policy makers and service providers pertinent to different points in the 'service delivery chain' including policy making, planning and budgeting; standard setting and enforcement; and performance monitoring.